The corporate culture survival guide - Schein, Edgar H. (Warren Bennis signature series., 2009)
The father of the corporate culture field and pioneer in organizational psychology on today's changing corporate culture. This is the definitive guide to corporate culture for practitioners. Recognized expert Edgar H. Schein explains what culture is and why it's important, how to evaluate your organization's culture, and how to improve it, using straightforward, practical tools based on decades of research and real-world case studies. This new edition reflects the massive changes in the business world over the past ten years, exploring the influence of globalization, new technology, and merger.